A ouvidoria na universidade pública : probabilidades e improbabilidades da comunicação - Camatti, Tassiara Baldissera (2014)
From the Systems Theory (Luhmann, 1996), which comprises communication as fundamental to the evolution of society through autopoietic and self-referential processes and relationships via interpenetration and mutual coupling, constituent propose our research focused on the University Ombudsman whose objectives were to investigate the role of the ombudsman in university organizations; analyze how the communication takes place in the university ombudsman and discuss the probabilities and improbabilities of communication in the university ombudsman. Our choice stems from the readings and surveys, including the university ombudsman as an appropriate theme for the investigated object of research. It is a social system in constant relationship with its surroundings and other systems, permeated by the complexity and it s various aspects: instability and balance, order and disorder, unity and difference. The theoretical survey we do is rooted primarily in the concepts of communication, and university ombudsman. The method chosen to provide us the reflections and insights needed is the Depth Hermeneutics, proposed by Thompson (1995), which allows us to understand, interpret and reinterpret the system and its surroundings. Regarding methodological procedures, we opted for document analysis, survey data - via questionnaire, interview and direct observation, beyond the historical and formal analysis/discourse in which we use content analysis proposed by Bardin (1977). The object of research was composed of the ombudsman public universities associated with the National Forum of University Ombudsmen and participants of the XIII National Meeting of FNOU, and our choice is justified by the predominance of listeners of public HEI in the event. At the end brings forth some considerations that express the result of reflections made. As the ombudsman, we understand that performs the function of agent with multiple roles: facilitator, educator and mediator, participating, even indirectly, the university system. As to the communication process, we find that is not based on consensus, but in diversity of interpretations arising from collective interactions via relational processes involving the interpenetration and mutual engagement to maintain the balance of the participating systems. In this context, language, means of dissemination and symbolically generalized media are important but do not guarantee the probability of communication. This, the watchdog of the public universities, mainly depends on human interaction, based on dialogue and the perception of how the various actors: applicants, employees/servants, teachers and managers use language, both verbal and nonverbal, to express yourself, understand the messages, including symbolic, relate them to their particular experiences and thus produce meaning.